KEHIDUPAN SOSIAL EKONOMI MASYARAKAT PETANI JAMBU METE DESA MATARAPE KECAMATAN MENUI KEPULAUAN KABUPATEN MOROWALI - Ardin, Ardin; Taena, La (Jurnal Penelitian Pendidikan Sejarah UHO, 2020)
ABSTRACT: The objectives of this study are: 1) To describe the social life of the cashew farmer community in Matarape Village, Menui Islands District, Morowali Regency; 2) To describe the economic life of the cashew farming community in Matarape Village, Menui Islands District, Morowali Regency. The type of research used in this research is descriptive qualitative research with the following stages: 1) Data collection techniques, namely observation, interviews and documentation; 2) Data analysis techniques, namely data reduction, data presentation and drawing conclusions. 3) Data validity consists of increasing persistence, triangulation and member checks. The results of this study indicate that: 1) The social life of the cashew farming community in Matarape Village, Menui Islands District, Morowali Regency can be seen in terms of: a) Education, the cashew farming community in Matarape Village is more dominated by an average level of education completing junior and elementary school. ; b) Health, diseases that often suffer are back pain, high blood pressure, fever, headaches and toothaches; c) Housing, which consists of: home ownership status, house foundation, house floor, house wall, house roof, house plapon, and house roof frame; d) Security, the cashew farmer community in the Matarape Village, MenuiIslands District is safe in the agricultural sector; 2) The economic life of the cashew farming community in Matarape Village, Menui Islands District, Morowali Regency can be seen in terms of: a) Capital, the cashew farming community already has capital, namely land and tools to cleantheir gardens; b) Expenditures, each cashew farming community is different depending on land area and ability to cultivate gardens; c) Workforce, only a small proportion of cashew farmers use labor because they have large gardens and need 3-7 workers; d) Crop yields every year, cashewfarmers get there is a significant difference between harvests in 2018 and 2019; e) Cashew farmer income, there is a significant difference where in 2018 the income is above an average of IDR 10,000,000 to IDR 67,150,000 with a purchase price of IDR 17,000 per Kg while in 2019 the income has greatly decreased to IDR < 5,000,000 and the highest income is IDR 38,402,000 with a cheap purchase price of IDR 14,000 per kg.Â